(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
Agricultural innovation platforms are increasingly seen as a panacea for mitigating the agricultural value chain challenges through enabling the co-evolution of different elements in the innovation process. A number of previous studies on IPs show processes for their formation and contribution to innovations. Very few studies have attempted to investigate the perceived benefits from platforms as important determinants for actor participation. Using a sample of 319 randomly selected farmers from one innovation platform in Uganda, it was established that the uncertain markets for the agricultural output, sources of inputs and agricultural information were perceived to be the key motivators for the formation of the platform. The study found a positive significant relationship between transaction cost challenges of environmental uncertainty and structural embeddedness (p<0.01) and frequency of interaction and structural embeddedness (p<0.05). On the other hand, environmental uncertainty, asset specificity and frequency of interactions were significantly correlated with relational embeddedness (p<0.05). However, the complexity of tasks in the value chain was not significantly correlated with structural and relational embeddedness (p≥0.05). It therefore means that to ensure effective participation and implementation of platform activities, efforts ought to be placed on fulfilling the platform’s promise as a forum for mitigation of transaction cost challenges such as inadequate markets for both output and inputs, customized products and inputs and lack of valuable agricultural information. Int. J. Agril. Res. Innov. & Tech. 8 (2): 1-12, December, 2018